Assessment of knowledge, attitude and practice in pharmacovigilance among clinical post graduate students in a teaching hospital, Vizianagaram, Andhra Pradesh, India - Nagisetty, Sindhura; Thotakura, Tulasi M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse drug reactions (ADR) are global problem causing morbidity and mortality. Good pharmacovigilance (PV) programme can address this problem. Under reporting of ADR is one of the obstacles for good PV. In order to achieve this, health professionals need to have enough Knowledge, attitude and practice (KAP) of ADR`s. The present study was conducted to assess KAP about PV among post graduate (PG) students. Methods: A self administered questionnaire validated by Lynn M consisting of 22 questions covering knowledge, attitude & practice about PV was distributed among PG students of clinical departments of MIMS College. Answering of the questionnaires was supervised directly. Filled questionnaires were analyzed by using Microsoft Excel spread sheet. Results: Evaluation showed an average of 52.3% correct and 47.7% incorrect knowledge about ADR`s and PV.50% students are not sure regarding occurrence of ADR.90% students are not been trained upon reporting of ADR`s. Our study found out that PG students have better attitude towards PV, but have improper knowledge & less awareness about PV. We also found lack of practice among the students. Conclusions: Imparting knowledge and awareness of PV among the PG students by means of continuous educational intervention can create better practice among PG students.